Technical and Economic Study of Fast Charging Systems Electric Heavy Equipment in Industrial and Port Areas - Rahmat Noval; Asep Apriana; Danardono Agus Sumarsono; Dedi Junaedi; Fuad Zainuri; Mohammad Adhitya; Muhammad Hidayat Tullah; Fuzi Rachmat Ramdhan (MBI, 2026)
The electrification of heavy equipment presents both an opportunity and a challenge for Indonesia’s industrial and port operations. Despite advancements in battery energy density and power electronics, the lack of efficient fast-charging infrastructure remains a critical bottleneck. This study evaluates the technical and economic feasibility of implementing high-power DC fast-charging systems for electric heavy machinery in port and industrial settings. Using HOMER Grid and MATLAB-based simulations, three charging configurations (90 kW AC, 250 kW DC, and 500 kW dual-gun DC) were analyzed. Results indicate that the 500 kW system reduces downtime by up to 70%, increasing equipment availability from 75% to 96%. Economic analysis shows a payback period of 4.8 years, internal rate of return (IRR) of 18.7%, and levelized cost of electricity (LCOE) of IDR 2,100/kWh. The findings support the deployment of modular fast-charging hubs to accelerate electrification in logistics and port sectors